Sustanciación de los procesos de adopción administrativo y judicial, vinculada al desistimiento de adoptantes por falta de celeridad procesal, en el cantón Guayaquil - Tomalá Bárcenas, Fernando Adrian (2022)
The present investigation was carried out based on certain social nuances that still remain in daily life requiring compliance, by the legal structure and what is embodied in the various rules of the matter, with the aim of substantiating the adoption processes based on speed. procedural as an act provided by the Constitution in judicial and administrative areas, which contribute to the effectiveness of adoptions. For this study, methodologies were used that allowed the analysis of the subject studied, which was based on a descriptive research with a non-experimental design through qualitative and quantitative instruments used to collect information; such as the survey, an evaluation technique aimed at judicial officials where the variable studied was the adoption process, where the importance of strict compliance with requirements based on legal regulations was confirmed; In effect, it is also required to substantiate processes in the stages, through a simplification of insignificant requirements for the administrative phase of adoption and its time for its completion; The fundamental application of the Principle of Higher Interest of the child to render a fair trial was also verified in the judicial sphere; Likewise, through the interviews, significant criteria were obtained by experts on the subject, factually weighing the regulations for the comprehensive protection of minors from their physical, cognitive and emotional development.........